Study of the Properties of Liquid Crystals - Aziz, Abdul Mohammad (Journal of Natural Sciences – Kabul University, 2024)
A liquid crystal has some of the order of solids and some of the fluidity of liquids, liquid crystals can exist in one of several possible states between solid and liquid at any moment. Liquid crystals are organic compounds that have long molecules and polar groups (NO2, -OR--CN, -NH2) are available at the end of them, sometimes parts like benzene rings are included in these materials. The molecules of these compounds have a linear structure; But for their central groups, the existence of double bonds between their diatoms is certain. The double bond prevents the rotation and stiffness of the molecules, taking into account their long axis ratio, these molecules contain groups with high polarization, and their dipole moment is high. Molecules in liquid crystal are not necessarily spatially ordered; But they can be oriented freely in three directions. In this review article, features such as their properties, structure and composition have been investigated.